Cover Image. (26th March 2019) - Emran, Abdullah Al; Chinna Chowdary, Brinda Reddy; Ahmed, Farzana; Hammerlindl, Heinz; Huefner, Antje; Haass, Nikolas K.; Schuehly, Wolfgang; Schaider, Helmut
Abstract : The cover image is based on the Original Research Magnolol induces cell death through PI3K/Akt‐mediated epigenetic modifications boosting treatment of BRAF‐ and NRAS‐mutant melanoma by Abdullah Al Emran et al., DOI:10.1002/cam4.1978 .